Pengaturan Tindak Pidana Korupsi Dalam Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana Serta Pengaruhnya Terhadap Kepastian Hukum - Situmorang, Nelly Esterina; Asphianto, Aan; Ridwan, Ridwan (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2025)
Introduction: Corruption, which already has a specific law, has become ambiguous after the enactment of Law 1/2023. Five articles were revoked and formulated in the Criminal Code as general criminal law, several articles experienced reduced sanctions. This shows that the political direction of eradicating corruption is increasingly unclear, both in terms of sanctions and the existence of corruption regulations. Purposes of the Research: This study aims to determine the basis for formulating the regulation of criminal acts of corruption in the New Criminal Code and to determine the legal certainty of the rules on criminal acts of corruption after being formulated into the New Criminal Code based on the principle of lex specialis derogat legi generali. Methods of the Research: The research method used in this writing is normative legal research. Normative legal research is research that prioritizes the discussion of legal theory and legal norms that exist in the legal system. Results of the Research: The formation of the New Criminal Code aims to recodify and reunify in one comprehensive law, by including the main criminal acts outside the Criminal Code. However, there is ambiguity because the government not only reformulated, but revoked five articles and reduced the sanctions. The author concludes that it should not be revoked or the sanctions reduced, because it can cause legal uncertainty and is contrary to the principles of law. This step is considered a setback in eradicating corruption which is an extraordinary crime. Therefore, what should be done is an update to the Corruption Law.